2015
DOI: 10.1186/s12884-015-0684-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal HIV infection and low birth weight and prematurity: a meta-analysis of cohort studies

Abstract: BackgroundTo assess the association between maternal human immunodeficiency virus (HIV) infection and low birth weight (LBW)/prematurity (PTD), we conducted a meta-analysis of cohort studies of HIV infected and uninfected women.MethodsSeveral English and Chinese databases were searched (updated to May 2015) to find the studies reporting infant outcomes associated with exposure to maternal HIV infection during pregnancy. Relevant articles were manually selected based on several inclusion and exclusion criteria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
113
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(147 citation statements)
references
References 62 publications
(25 reference statements)
15
113
2
6
Order By: Relevance
“…16 Interestingly, Xiao and co-workers, in their meta-analysis, found that ARV drug usage did not significantly change the association of maternal HIV exposure to ARV drugs with LBW. 11 In contrast, one study in South Africa found that HIV-positive mothers not on ART or ARV prophylaxis delivered significantly LBW infants compared with the HIV-positive mothers on ART or ARV prophylaxis. 17 It is worth noting that, in our study, HIV-positive women not on ART or ARV prophylaxis significantly delivered babies with birthweight < 1 000 g. The findings in our study could be due to the fact that the HIV-positive mothers not on ART might have had a lower CD4 cell count and higher HIV RNA viral load, which might have contributed to extremely LBW (< 1 000 g) babies.…”
Section: Discussionmentioning
confidence: 92%
“…16 Interestingly, Xiao and co-workers, in their meta-analysis, found that ARV drug usage did not significantly change the association of maternal HIV exposure to ARV drugs with LBW. 11 In contrast, one study in South Africa found that HIV-positive mothers not on ART or ARV prophylaxis delivered significantly LBW infants compared with the HIV-positive mothers on ART or ARV prophylaxis. 17 It is worth noting that, in our study, HIV-positive women not on ART or ARV prophylaxis significantly delivered babies with birthweight < 1 000 g. The findings in our study could be due to the fact that the HIV-positive mothers not on ART might have had a lower CD4 cell count and higher HIV RNA viral load, which might have contributed to extremely LBW (< 1 000 g) babies.…”
Section: Discussionmentioning
confidence: 92%
“…Nonetheless, maternal HIV infection is a known risk factor for preterm delivery, which in turn substantially increases the risk of child mortality and morbidity including suboptimal growth. [22, 23] As such, identifying and providing appropriate care to premature infants should be integral to strategies aimed at optimizing HEU child health.…”
Section: Discussionmentioning
confidence: 99%
“…10 Brocklehurst et al and Xiao PL reported that LBW and PTD were associated with maternal HIV infection. 11,12 Habib et al, has also shown an association between maternal HIV status and preterm labour. 13 19,20 There was an increased incidence of adverse foetal outcomes in terms of IUD, still birth and preterm birth -20% in HIV seropositive patients in contrast to 2.5% in HIV seronegative pregnancies.…”
Section: Discussionmentioning
confidence: 94%